The effectiveness of mental health psychoeducation to improve mental health literacy of residents of Soka, Mertelu, Gedangsari, Gunungkidul - Hanifah Sholihah; Yayah Siti Nurkhomariyah; Ali Maulana Akbar; Irma Dwiyanti; Irfan Hidayat; Ainul Luthfia Al-Firda; Muhammad Irsyad Alfarisi (Faculty of Psychology, Universitas Negeri Yogyakarta, 2026)
Mental health is a crucial component of overall health that significantly influences quality of life and societal well-being. However, low levels of mental health literacy remain a persistent issue in many rural areas, including Soka, Mertelu, Gedangsari, Gunungkidul. This limited understanding may lead to delays in recognizing psychological problems, increased stigma, and underutilization of mental health services. Psychoeducation is considered a preventive and promotive approach aimed at improving knowledge, attitudes, and public understanding of mental health. This study aimed to examine the effectiveness of psychoeducation in enhancing mental health literacy. This study employed a quasi-experimental design without a control group, using a one-group pretest-posttest design. The participants consisted of 19 residents of Soka, Mertelu, Gedangsari, Gunungkidul. Data were collected using a multiple-choice mental health literacy and analyzed using a paired sample t-test with IBM SPSS version 23. The results showed a t-test value of -5.112 with a significance level of 0.000, indicating a statistically significant effect. Therefore, it can be concluded that mental health psychoeducation is effective in improving mental health literacy among the community in Soka, Mertelu, Gedangsari, Gunungkidul.